Pengaruh Modal Kerja Terhadap Pendapatan Pengumpul Gula Aren Cibuluh Di Kabupaten Lebak - Ferdian Arie Bowo; Heru Herbowo; Hayatinufus Siatan; Maesaroh . (E-Journal Studia Manajemen, 2012)
Lebak Cibuluh collectors Palm Sugar is the backbone of the economy of the population in the region and surrounding areas that can create jobs and increase income. In its efforts to increase revenue collection will require effective management of working capital and efficient. The method used by the authors is a quantitative method with quantitative descriptive approach, In this study the authors used financial data collecting palm sugar for two months, then the sample used is sugar revenue data, purchasing, and sales per week. This sample is used because the recording is done by manually collecting palm sugar and are not recorded administratively. The decision to accept or reject the hypothesis can be done by comparing the tcount with ttabel. Tcount in this study is 7217. Because tcount> ttable, (7.217> 2.365), then the accepted hypothesis is that there is the influence of working capital to revenue collection in the district of palm sugar Cibuluh lebak.